SUBCUTANEOUS DRAINAGE IN LYMPHEDEMA TREATMENT IN PROSTATE CANCER PATIENTS - Ferreira, Cátia Manuela Azevedo; Santos, Diana Moura; Real, Vanessa Tatiana Vieira; Marques, Paulo Alexandre Oliveira (Cogitare Enfermagem, 2024)
Introduction: this article sought to deepen knowledge about the subcutaneous lymphatic drainage technique as a form of palliative treatment for secondary lymphedema in prostate cancer patients. Development: literature review carried out between November 13 and 17, 2023, in the Medline and CINHAL databases. The literature supporting this analysis is scarce, both in terms of studying the technique on site and standardizing the procedure. These considerations explain the benefits that the technique offers in improving men’s quality of life, in the sexual, psychological and social contexts, and in the economic repercussions. Conclusion: subcutaneous lymphatic drainage is a technique that is little known, and little used in clinical practice, but it is an option to consider in the treatment of secondary lymphedema in a palliative context, as it can improve the patient’s quality of life.